Trade Liberalization and Environmental Taxation in Federal Systems - Per G. Fredriksson; Xenia Matschke (Center for Economic Studies and ifo Institute (CESifo), 2014)
The literature on trade liberalization and environment has not considered federal structures. This paper shows how the design of environmental policy in a federal system has implications for the effects of trade reform. Trade liberalization leads to a decline in pollution taxes regardless of whether pollution taxes are set at the federal (centralized) or local (decentralized) level, and it increases social welfare. The effect under a decentralized system is smaller than if these taxes are set by the federal government, and pollution emissions therefore decline in this case. Moreover, majority bias interacts with trade liberalization if federal taxes are used.
Keywords: F10; H20; H70; Q20; 330; trade and environment; environmental policy; trade liberalization; environmental federalism; political economy; majority bias; social welfare